ANALISIS PENGARUH KENDARAAN ODOL TERHADAP TINGKAT KECELAKAAN DI JALAN TOL - Enggar Oktarinda; Nuzul Barkah Prihutomo; Eka Olivia Maulani (Politeknik Negeri Jakarta, 2022)
Semarang ABC toll road is an inner-city toll road of Semarang connecting the West, East, and South areas of Semarang City. The toll road is a crucial road for land transportation in Java and yet passed by many overloaded and over-dimension vehicles. Overloaded and over-dimension vehicles (ODOL) on toll roads is categorized as a traffic violation that harms various parties such as disrupting the smooth traffic flow due to low speeds and affecting toll road maintenance costs due to ODOL vehicle loads, and Accident rates involving overloaded vehicles. This study aims to examine the effect of ODOL vehicles on the Accident rate on toll road. The study used a regression test with SPSS software. The results of the study show there is an influence between ODOL vehicles and the level of traffic accidents on toll road by 32%. From the JM Digimap application, case studies of accidents involving ODOL vehicles on toll road can disrupt the smooth traffic flow and reduce the average passing speed by up to 12%. Keywords: Accident Rates, Over-dimension, Overloading, Traffic Violation.